OUTCOME OF GRAHAM PATCH OMENTOPEXY IN THE MANAGEMENT OF PERFORATED DUODENAL ULCER - KHAN, MA; KHAN, WY; KHAN, MU; HUSSAIN, E; KHAN, S; USMAN, SZ (Biological and Clinical Sciences Research Journal, 2024)
Perforated duodenal ulcer remains a surgical emergency with significant morbidity and mortality. Graham’s patch omentopexy is a commonly performed procedure for its management. Evaluating the outcomes of this technique is crucial for improving patient care. Objective: To examine the outcomes of Graham’s patch omentopexy in managing perforated duodenal ulcers, focusing on postoperative complications. Methods: This study included 45 patients diagnosed with perforated duodenal ulcers who underwent Graham’s patch omentopexy from June 2023 to December 2023. The outcomes were assessed in terms of postoperative complications, including wound infection, wound dehiscence, pneumonia, bile leakage, abdominal abscess, and mortality. Results: The mean age of the patients was 46.49 ± 9.58 years. Postoperative complications included wound infection in 14 patients (31.3%), wound dehiscence in 13 patients (28.9%), pneumonia in 6 patients (13.3%), bile leakage in 5 patients (11.1%), abdominal abscess in 6 patients (13.3%), and mortality in 1 patient (2.2%). Conclusion: Graham’s patch omentopexy is an effective technique for managing perforated duodenal ulcers; however, complications such as wound infection, dehiscence, pneumonia, bile leakage, abdominal abscess, and mortality can occur. Further studies are needed to identify factors associated with these complications to optimize patient outcomes.